2015
DOI: 10.1039/c5nr05826k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of doxorubicin on citrate-capped gold nanoparticles: insights into engineering potent chemotherapeutic delivery systems

Abstract: Gold nanomaterials have received great interest for their use in cancer theranostic applications over the past two decades. Many gold nanoparticle-based drug delivery system designs rely on adsorbed ligands such as DNA or cleavable linkers to load therapeutic cargo. The heightened research interest was recently demonstrated in the simple design of nanoparticle-drug conjugates wherein drug molecules are directly adsorbed onto the as-synthesized nanoparticle surface. The potent chemotherapeutic, doxorubicin ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…Therefore, it is very necessary to develop a drug carrier with good biocompatibility and high drug loading ability. In recent years, a lot of nanomaterials, such as quantum dots [12,13], chitosan [14,15] silicon nanomaterials [16,17], polymeric nanomaterials [18][19][20], fluorescent nanoparticles [21][22][23][24], and metal nanomaterials [25][26][27][28][29][30] were developed as DOX transport vectors for tumor diagnosis and therapy. Gold nanomaterials have been widely used due to their unique chemical and optical properties, low toxicity, good biocompatibility, and surface modification of control ability [31,32] among these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very necessary to develop a drug carrier with good biocompatibility and high drug loading ability. In recent years, a lot of nanomaterials, such as quantum dots [12,13], chitosan [14,15] silicon nanomaterials [16,17], polymeric nanomaterials [18][19][20], fluorescent nanoparticles [21][22][23][24], and metal nanomaterials [25][26][27][28][29][30] were developed as DOX transport vectors for tumor diagnosis and therapy. Gold nanomaterials have been widely used due to their unique chemical and optical properties, low toxicity, good biocompatibility, and surface modification of control ability [31,32] among these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The second is to incubate GNPs with DOX for at least 24 h [29]. The third is to replace citrate conjugated on the surface of gold nanoparticles (GNPs) by DOX [30]. Although these DOX-conjugated GNPs have been used in tumor therapy, the application is still limited due to the lack of sufficient specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The quenching phenomenon mainly depended upon the partly overlap of the fluorescence band of the PFBT (450–700 nm) with the absorption band of the HGCNs (500–700 nm) (Figure c), as required for FRET . Whereas upon NIR irradiation, the fluorescence signals of PFBT were dequenched due to the increase of the distance between PFBT and HGCNs . As a result, PFBT could be utilized as the real‐time tracing probe since the fluorescent signals could be turned “OFF” (quenched) when transported in circulatory system, and then be turned “ON” (dequenched) by NIR laser when delivered to the determined tumor sites.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the number of protonated amino groups present in the drug backbone (four in the case of BNIPSpm when compared to two in Previous studies have shown that doxorubicin can be absorbed onto colloidal gold surfaces and electrostatically attached. In the case of this drugs, it has been shown that the hydrophobic moieties within the structure drive the molecule towards the gold surface and secondly the charge within the compound resulting from the one primary amine allow for electrostatic attachment [39]. The mechanism of bisnaphtalamide drug attachment onto the HNP surface may undergo a similar mechanistic approach to attachment, however, the multiple amine charges resulting from the polyamine chain far outweigh the hydrophobicity of the naphthalamide moieties within the drug structure resulting in a freely soluble drug compound, unlike in the case of doxorubicin.…”
Section: Hnp-drug Conjugation and Characterisationmentioning
confidence: 99%